(NrEAKCIQ pUDOWIKA (B/s - (NkONOWALOWA(B, (NiRINA wADIMOWNAs; (NbURNAEWA(B, (NlILIQ aHMETOWNAs ((NkAZANX (B:s (NiZD(B-(NWO kAZANSKOGO UN(B-(NTA(B,s, 1991)
(NbIBLIOGR(B.: (NS(B. 120 - 146 (505 (NNAZW(B.)s
Keywords: (NfOSFORORGANI^ESKIE SOEDINENIQs; (NhIMIQs